If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3 = x + -15 Reorder the terms: -3 + 4x = x + -15 Reorder the terms: -3 + 4x = -15 + x Solving -3 + 4x = -15 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 4x + -1x = -15 + x + -1x Combine like terms: 4x + -1x = 3x -3 + 3x = -15 + x + -1x Combine like terms: x + -1x = 0 -3 + 3x = -15 + 0 -3 + 3x = -15 Add '3' to each side of the equation. -3 + 3 + 3x = -15 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = -15 + 3 3x = -15 + 3 Combine like terms: -15 + 3 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| a-5=66 | | x^2-6x+1=2-6x | | 5x-6=1-6x | | 7x-6=1-5x | | 6x^2+20x+12=0 | | x^2-5x+4=19-3x | | 4x+8-x+3=2x+23 | | y^2+3y+yx+3x=0 | | 10x-37=-87 | | x=8-3x | | (x-8)=4 | | (X*0.1)+X=100 | | (100*0.1)+100=X | | X*0.1=100 | | 6x+11=2x-1 | | (-3)(3+2x)+4x^2+1(1-x)=-11 | | 18x-x^2=71 | | 3x-15y=0 | | 2a+11=15 | | 36*(25+48)-16*22= | | 2x+36=6x+3 | | 7+5x=42 | | H=-4.9t^2+80t | | 1+3x=16-2x | | 5a^2+22a+21=0 | | 2x+8=3x+6+8 | | 2y^2+19y=-24 | | x^3-15x^2+800=0 | | 6-8x=47-15x | | 4v-5=v+4 | | (x)(x+1)=14(2x+1)+44 | | x+786(y+z)=2526 |